22 Assessment of markers of cardiac toxicity following combined treatment of cardiomyocytes with epirubicin and trastuzuma. (30th September 2020) - Tonry, C; Mhic Donncha, E; Scott, H; Harbison, M; Bell, D; Watson, C
Abstract : Background: Advancements in cancer therapy have significantly improved long-term survival rates of those with breast cancer. The addition of epirubicin treatment prior to standard trastuzumab treatment has been shown to slow progression of disease, reduce mortality and extend duration of survival in patients with HER2+ Breast Cancer. However, both drugs have off target cardiotoxic effects. Currently echocardiography is the only standardised diagnostic measure for detecting cardiac dysfunction. However, this is often after significant irreversible cardiac damage has occurred. There is an emerging need for blood-based biomarkers to aid in diagnosing subclinical cardiac dysfunction and to stratify those at risk prior to therapy. Methods: AC16 human cardiomyocytes were treated with Epirubicin (2.6 ug/ml) and Trastuzumab (150 ug/ml), both together and in monotherapy, over 10 hr and 26 hr time-points. Cell viability was assessed via MTT cell viability assay. Protein and gene expression of Troponin I and BNP were assessed via western blot analysis and RT-PCR. Western blot analysis and fluorescent microscopy staining of oxidative stress markers was also carried out to elude to the potential mechanisms of cardiac damage. Results: Morphological changes occurred in all cells treated over 26 hrs, particularly with combined treatment. Cardiomyocytes treated with epirubicin alone showed the most significant reduction in cell viability compared to control (p ≤ 0.01**). Some increase in BNP and Troponin I expression was observed in cardiomyocytes treated with both epirubicin and trastuzumab. Pre-treatment of cardiomyocytes with recombinant BNP ameliorated chemotherapy-induced cell death in cardiomyocytes to some degree, however the effect was not significant. Conclusion/Implications: Combined treatment with epirubicin and trastuzumab exacerbates chemotherapy-induced cardiotoxicity. Troponin I and BNP are biomarkers that could be used as a diagnostic tool for prediction of subclinical chemotherapy-induced cardiotoxicty but further work is required to establish their true clinical utility.